Self-assembly of hybrid organic-inorganic polyoxovanadates: functionalised mixed-valent clusters and molecular cages - SCHMITT, WOLFGANG (My University, 2012)
Herein we report the intra- and inter-molecular assembly of a {V 5O 9} subunit. This mixed-valent structural motif can be stabilised as [V 5O 9(L 1-3) 4] 5-/9- (1-3) by a range of organoarsonate ligands (L 1-L 3) whose secondary functionalities influence its packing arrangement within the crystal structures. Variation of the reaction conditions results in the dodecanuclear cage structure [V 12O 14(OH) 4(L 1) 10] 4- (4) where two modified convex building units are linked via two dimeric {O 4V IV(OH) 2V IVO 4} moieties. Bi-functional phosphonate ligands, L 4-L 6 allow the intramolecular connectivity of the {V 5O 9} subunit to give hybrid capsules [V 10O 18(L 4-6) 4] 10- (5-7). The dimensions of the electrophilic cavities of the capsular entities are determined by the incorporated ligand type. Mass spectrometry experiments confirm the stability of the complexes in solution. We investigate and model the temperature-dependent magnetic properties of representative complexes 1, 4, 6 and 7 and provide preliminary cell-viability studies of three different cancer cell lines with respect to Na 8H 2[6]?36H 2O and Na 8H 2[7]?2DMF?29H 2O.
PUBLISHED
Keywords: Chemistry